Finite-time stability of singular switched systems with a time-varying delay based on an event-triggered mechanism - Yidan Wang; Li Xiao; Yanfeng Guo (AIMS Mathematics, 2023)
In this paper, the finite-time stability (FTS) of singular switched systems that have time-varying delays and perturbations is investigated. First, the concept of the FTS of time-varying delay singular switched systems is given, and a specific event-triggered mechanism is proposed. Then, a state feedback mechanism is proposed based on the event-triggered mechanism. Second, using the L-K function and state space decomposition, adequate criteria for the FTS of singular switched systems are found. Sufficient requirements are also presented for meeting the finite-time stable $ H_∞ $ performance index $ γ $.